PENANGGULANGAN PEREDARAAN NARKOTIKA DIKALANGAN PELAJAR KUTAI TIMUR - Nunuk Andayanti (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT The progress achieved in the reform era is quite promising, but on the other hand there are still worrying issues, especially regarding the behavior of some of our young generation who are trapped in drug abuse both consuming and distributing it. Narcotics abuse is a national and international problem, because it has a negative impact on the lives of people, nations and countries and their addicts, who are mostly students. Victims of narcotics abuse in Indonesia are increasing and are not limited to groups of people who are able, given the high price of narcotics, but also has penetrated the constraints of low economic society. This can happen because narcotics commodities have many types, from the most expensive ones that can only be bought by the elite or celebrities, to the cheapest ones that are consumed by low economic groups. Misuse and dangers of narcotics Narcotics among adolescents is undeniable that there are still many in the environment around us. The impact of narcotics on health and the future is indeed not insignificant. Many will be sacrificed because of narcotics abuse. Based on the background description of the problem above, the problems in this paper are: (1) What is the Countermeasure of Narcotics Circulation in East Kutai Students? (2) What is the legal process for narcotics dealers in East Kutai Students? The conclusions of this paper (1) The handling of narcotics illicit trafficking needs to be done comprehensively and multidimensionally. Trying to dispel the view that the problem of narcotics abuse and illicit trafficking is not just a matter of the government, but is a problem that must be tackled together. Prevention and eradication of narcotics abuse and illicit trafficking is carried out by building community-based prevention efforts, including through school and non-school education. electronic and print mass media, including advances in internet technology and communication tools, which need to be utilized to the maximum extent possible in providing information to the public at large, Criminal Provisions in Law Number 35 Year 2009, concerning Narcotics are regulated in Articles 110 through Article 148, as with most Criminal Acts outside the Criminal Code the formulation of Criminal provisions in several respects is different from the criminal formulation in the Criminal Code. (2) The implementation of the child protection law and attention to the legal process against problematic children by referring to law number 11 of 2012 as a legal umbrella that must be carried out both directors and Restorative Justice efforts, This is humane and takes into account the rights of children by involving various related parties to reach agreement and settlement while still paying attention to certain criteria. Strictly speaking, law enforcement officials must continue to refer to Article 16 paragraph (3) of Law No. 23 of 2002 which is amended by Law No. 35 of 2016 that protects children, namely that the arrest, detention or criminal offenses of children are only carried out if they are in accordance with applicable law and can only be done as a last resort. Keywords: Countermeasures, Narcotics Circulation, Students